2014
DOI: 10.1080/15459624.2013.816432
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Formaldehyde Exposures in an Academic Gross Anatomy Laboratory

Abstract: This report describes efforts over a more than a 15-year period to improve air quality and reduce exposures to formaldehyde during anatomical dissections at the Yale University School of Medicine, including first-year medical student gross anatomy classes. During this time, a number of steps were taken to improve general ventilation system efficiency and work practices in the original facility. Subsequently, during the design phase for a new research and teaching building, a new anatomical laboratory was plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
3
10
1
Order By: Relevance
“…Normally, 10 air changes per hour was set up for the specific room including gross anatomy dissection room (Yamato et al 2005). Although the ventilation rate of this study was rather lower those of reports which were 9.8 (Keil et al 2001) or 20.5 air changes per hour (Klein et al 2014), the FA concentration in our fixative solution was 5 % FA and this was lower than Keil's study. Normally, preserved cadavers were prepared with similar embalming fluid containing approximately 10 % FA.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Normally, 10 air changes per hour was set up for the specific room including gross anatomy dissection room (Yamato et al 2005). Although the ventilation rate of this study was rather lower those of reports which were 9.8 (Keil et al 2001) or 20.5 air changes per hour (Klein et al 2014), the FA concentration in our fixative solution was 5 % FA and this was lower than Keil's study. Normally, preserved cadavers were prepared with similar embalming fluid containing approximately 10 % FA.…”
Section: Discussioncontrasting
confidence: 83%
“…The local exhaust ventilation was controlled vapor of organic liquid and kept the occupational exposure limit below 0.1 ppm. In our study, the room's ventilation flow rate improved the FA concentration in the indoor air as in a report of Klein et al (2014). The activity and region of dissection involved the level of FA indoor air; there was previous report that the FA concentration in indoor air were ranged from 0.48 to 1.11 ppm during systemic anatomy and from 0.21 to 0.23 ppm during neuroanatomy, respectively (Takayanagi et al 2007).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, after 1 and 3.5 months of contact, this research showed that the mutagenicity not only occurred after the first month, but also increased after that. These data reinforce the importance of improving air quality and reduce exposures during anatomical dissections and anatomy practical classes (7). It is important to stress that occupational exposure to FA evaluated by other investigations (1,26-29) presented greater contact time with formaldehyde and its concentration in the air was higher than those found for anatomy students, which differentiate them from this research.…”
Section: Discussionsupporting
confidence: 77%
“…Due to increased exposure, which occurs in factories, hospitals and universities, several researches have been studying the potential toxicity and the safe levels for human beings (6). At the same time, efforts have been made to improve air quality and reduce exposures during anatomical dissections and anatomy classes (7). …”
Section: Introductionmentioning
confidence: 99%